Pyruvate Kinase Deficiency and Developments In its Treatment - Meducator, The; Patel, Kashyap; Sikder, Omaike; Hariharan, Nikhil; Zhang, Jeff (The Meducator, 2019)
Pyruvate kinase (PK) is an enzyme involved in ATP production in the glycolytic pathway. PK deficiency is a rare, autosomal recessive disorder that manifests with hemolytic anemia of variable severity, partly due to an insufficiency of ATP production in erythrocytes. Its exact prevalence is unknown due to lack of awareness and challenges in making the diagnosis of PK deficiency. Current treatments for PK deficiency include blood transfusion and splenectomy, which focus on temporarily alleviating anemia and reducing hemolysis, respectively. Due to the rarity of this condition and its variable severity, a systematic treatment protocol for novel therapies is difficult to compile and validate. Oral administration of mitapivat, an allosteric activator of erythrocyte PK, is a novel treatment. Despite its promising effects on the hemoglobin levels in PK deficient patients, mitapivat’s efficacy and safety profiles must be determined through randomized controlled trials.